Expansion of Diversion Regulations in the Trial of Children in Conflict with the Law - Setyawan, Vincentius Patria; Kristianti, Anastasia Priska (Universitas Muhammadiyah Palembang, 2022)
Diversion is a sort of alternative dispute resolution that diverts child cases away from the conventional legal system and toward more informal means of conflict settlement. Children who are threatened with incarceration for a term of less than seven (seven) years and who have not committed a crime may be eligible for a diversion mediation process under Article 7 paragraph (2) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This process may be applied to cases in which the child is not guilty of a crime. The structure for diverting cases that is included in the Supreme Court Regulation represents an expansion of the legal meaning. Nevertheless, the Supreme Court Regulation in this instance needs to be in compliance with the provisions of the law that is already in place. In this study, a qualitative research method was combined with an approach based on literature and legislation. According to the findings of the study, developments regarding diversion regulations are contained in Supreme Court Regulation Number 4 of 2014 concerning Guidelines for the Implementation of Diversion in the Juvenile Criminal Justice System. As a result, this supreme court regulation permits diversion in terms of criminal acts that are punishable by imprisonment of 7 years or more in the form of a subsidiary.